Allelic differences affecting invariant chain dependency of MHC class II subunit assembly. - Bikoff, E; Germain, R; Robertson, E (1995)
The conserved invariant chain associates with highly polymorphic alpha and beta subunits guiding class II transport through the secretory pathway. Early associations of these three polypeptides inside antigen-presenting cells are poorly understood. The present experiments provide a detailed picture of the structure and fate of class II alpha and beta subunits in invariant chain mutants possessing different MHC haplotypes. In the absence of invariant chain, A alpha bA beta b is predominantly expressed as free A alpha b and A beta b chains by both splenocytes and activated LPS/IL-4 blasts, confirming that A alpha bA beta b assembly is strongly dependent on invariant chain coexpression. A quite different situation exists with respect to other allelic products. In the absence of invariant chain, A alpha kA beta k, E alpha kE beta k, and A alpha dA beta d molecules assemble efficiently and are conformationally similar to mature wild-type heterodimers. The contribution of invariant chain to subunit assembly thus differs for allelic variants, suggesting that sequential associations of alpha, beta, and invariant chain may be affected by polymorphic differences.